Winners and losers of school choice: Evidence from Rio de Janeiro, Brazil and Santiago, Chile. (March 2015) - Alves, Fatima; Elacqua, Gregory; Koslinki, Mariane; Martinez, Matias; Santos, Humberto; Urbina, Daniela
Highlights: High-SES families in Santiago are more likely to choose schools outside of their neighborhoods. In Rio de Janeiro there are no significant differences across SES groups in distance traveled to schools. In both cities, high-SES parents are more likely to choose high achieving schools. The differences across SES groups are more pronounced in Santiago than in Rio. Abstract: School choice is a controversial topic in the education debate. Proponents argue that choice would open up opportunities to disadvantaged families. Critics counter that choice may exacerbate inequities as advantaged parents are more likely to choose the best schools. Rio de Janeiro and Santiago provide unique institutional contexts in which to explore how choice may affect equity. We use datasets with information on home addresses to compare the choices of parents with different backgrounds. We find that disadvantaged parents in both cities are less likely to choose high achieving schools. The differences are more pronounced in Santiago than in Rio. These results suggest that choice policies will likely not reduce inequities and the design of the program influences behavior.